(3YeOI GdcJGHs - (3GdeYR Hf HGOjS Hf GdefUhQ GdUfgGLj , J (B454 (3g` s
(3ChdgG (B:s
(3ef Chd GdehLhO agQS GdHGH GdChd aj aVd GdYde hGdNW s
(3BNQgG (B:s
(3UaI GdQSe hgh EPG La GdLdO GMJLJ Gdj Cf JfSN GdcJGH HGdSja hJOYg Hjf jOjc hJCNP eSWQI aJVYgG Ydi MGaJj GdcJGH s
(3heYg ahGFO WHjIs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeYGQa GdYGeIs